Nature and Level of Support to the Community based Fisheries Activities in the Coastal Towns - C. Cabalbag, Antonio; Jane A. Cabalbag , Sally (International Journal of Psychosocial Rehabilitation, 2020)
This study generally aimed at determining the nature of support institutions to community-based fishery activities, specifically, the profile of respondents, actual support to fisherfolks along Technical services, supply services for fisheries productivity, and supply infrastructure facilities; encountered fisherfolks problems and proposed intervention program. Respondents utilized in the study were chairpersons and members of the different accredited fisherfolk associations in Northern Cagayan. Structured questionnaires and an interview guide were employed to gather data. More so, total enumeration was employed. To obtain data on the problems encountered, focused group discussion was used. Result revealed that most of the respondents engaged in fish cage operation, marine fishing, grow-out tilapia, aquasilvi and oyster culture are males, married, high school graduate with capitalization of 41,000-50,000. Municipal C had the highest distribution of fisherfolk association members. The respondents were found to be financially assisted; however, as regards supply support along fingerlings, equipment, and facilities, tilapia and bangus are the fingerlings distributed in the different municipalities but are supported as to equipment and facilities. Further, the most pressing problem encountered by the respondents is on project management and prompt replacement of damaged items. Finally, to strengthen the support mechanism of the government on the fisher folk community, the program of inclusive planning as intervention was raised.